Pelatihan Terpadu untuk Meningkatkan Argumentasi Ilmiah - Tri Ayu Lestari; Fakhruddin Fakhruddin; Andi Agung Wahyu Utama (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
In the digital era, the development of artificial intelligence (AI) technology increasingly influences education, requiring students to possess stronger critical thinking and scientific argumentation skills. This Community Service (PKM) activity aimed to enhance the scientific argumentation abilities of the fifth-semester students of the Physics Education Program at Universitas Nusa Cendana. The training involved 25 students over five days, consisting of three main phases: demonstration and brainstorming, mentoring, and scientific argumentation practice through structured debates and scientific presentations. Evaluation results indicate that the training successfully improved students' understanding of scientific argumentation, with an average score of 4.35 for skill improvement and 4.12 for confidence enhancement. Seventy percent of participants stated that the training positively impacted their skills, while 88% felt that the materials were sufficient. However, challenges in managing group discussions and the training duration were identified, needing improvements for future implementations. With a hands-on approach and interactive learning, this training proved effective in enhancing students' critical thinking, academic communication, and scientific argumentation skills. This PKM initiative could serve as a model for developing innovative learning methods to prepare competent future educators in the digital age.